The secret prophecy - Brennan, Herbie (Balzer + Bray, 2012)
Edward Michael "Em" Goverton, mourning the death of his father, receives help from family friend Charlotte and a mysterious stranger named Victor after he uncovers information about a world-shattering conspiracy his dad was investigating and becomes the target of armed men, who will do anything to make sure their plan is not ruined.